2021
DOI: 10.3390/jcdd8110156
|View full text |Cite
|
Sign up to set email alerts
|

Post-Acute Sequelae of COVID-19 and Cardiovascular Autonomic Dysfunction: What Do We Know?

Abstract: Post-acute sequelae of SARS-CoV-2 (PASC), or long COVID syndrome, is emerging as a major health issue in patients with previous SARS-CoV-2 infection. Symptoms commonly experienced by patients include fatigue, palpitations, chest pain, dyspnea, reduced exercise tolerance, and “brain fog”. Additionally, symptoms of orthostatic intolerance and syncope suggest the involvement of the autonomic nervous system. Signs of cardiovascular autonomic dysfunction appear to be common in PASC and are similar to those observed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
92
0
4

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 87 publications
(97 citation statements)
references
References 94 publications
1
92
0
4
Order By: Relevance
“…Postural orthostatic tachycardia syndrome may have an immunological cause. Many patients describe a postviral onset, [29][30][31][32] and 15%-20% of patients with POTS report a history of an autoimmune disorder such as Hashimoto thyroiditis, rheumatoid arthritis or Sjögren syndrome. 4 Recently, numerous cases of POTS 33 and other forms of sinus tachycardia (e.g., inappropriate sinus tachycardia) 34 after a SARS-CoV-2 infection have been reported.…”
Section: What Is the Pathophysiology Of Pots?mentioning
confidence: 99%
“…Postural orthostatic tachycardia syndrome may have an immunological cause. Many patients describe a postviral onset, [29][30][31][32] and 15%-20% of patients with POTS report a history of an autoimmune disorder such as Hashimoto thyroiditis, rheumatoid arthritis or Sjögren syndrome. 4 Recently, numerous cases of POTS 33 and other forms of sinus tachycardia (e.g., inappropriate sinus tachycardia) 34 after a SARS-CoV-2 infection have been reported.…”
Section: What Is the Pathophysiology Of Pots?mentioning
confidence: 99%
“…In the United States, a study of 2 million COVID-19 survivors identified that 23% of convalescent patients had continued symptoms beyond four weeks, and, as also found in the UK ( 16 ), represented all age groups and included patients whose initial SARS-CoV-2 infection was asymptomatic or mildly symptomatic ( 15 , 17 , 18 ). Symptoms related to cardiovascular autonomic dysfunction seem to be common in patients affected by long COVID syndrome ( 19 ). Moreover, pre-existing cardiovascular risk factors, socio/economic disparities, and comorbidities concur in amplifying the adverse, long-term consequences of COVID-19 (syndemic) ( 20 23 ).…”
Section: Introductionmentioning
confidence: 99%
“…44 Since the onset of the COVID-19 pandemic, an increasing number of case reports about the occurrence of POTS secondary to a COVID-19 infection have emerged. [24][25][26][27][28][29][30] Several hypotheses about possible pathomechanisms of POTS or dysautonomia in general after COVID-19 infection have been proposed: imbalance of the renin-angiotensin-aldosterone system, 26,29 brainstem involvement, 43,45,46 autoreactivity to antibodies against SARS-CoV-2, 25,43,47 dyshomeostasis of immune response 42,44 and denervation of peripheral sympathetic nerve fibers. 26,43,42 This study has some limitations.…”
Section: Muscle Painmentioning
confidence: 99%